Tax Mechanisms of Economic Development and the Improvement of Migration Situation in the Russian Arctic - Sukneva, Svetlana A.; Nikulkina, Inga V. (International Journal of Economics and Financial Issues, 2017)
The paper deals with the economic and demographic development of the Arctic regions of Russia. It shows the features of demographic dynamics consisting in a sharp reduction of the population, a significant contribution that migration plays in the formation of the population. Based on the analysis of two population surveys of the Arctic regions of the Republic of Sakha (Yakutia) the paper presents the views of residents about their everyday problems that the people are mostly concerned about, the causes of migration, the expectations of changes in migration plans of their children. A conclusion is made about the necessity of state support of the Arctic regions, solving social and economic problems of life in the Arctic, and, above all, the preservation of the population, improving the conditions and quality of life, supporting traditional economies and way of life of the Arctic’s indigenous peoples. In order to create favourable tax conditions in the Arctic zone of the Russian Federation, the authors propose to create an enabling system of taxation and customs regulations with the aim of stimulating investment, entrepreneurship activities and enhancing the effectiveness of the implementation of projects aimed at socio-economic development of the Russian Arctic. Keywords: Arctic, migration, state support, tax regulation JEL Classifications: H10, R23